Venom-induced consumption coagulation in a hematotoxin snake bite in East Java, Indonesia: A case report - Sasmito, Priyo; Mulyatiindo, Leli; Bernadus, Janno Berty Bradly; Arifani, Nisa; Astuti, Novia Dwi; Prasetya, Fika Indah; Librianty, Nurfanida; Wirawan, Nandar (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Located in Southeast Asia, Indonesia is one of the countries with the highest incidence of fatal snakebites in the world. Difficulty in identifying snake species and limited availability of antivenom often pose challenges in treating snakebites. Purpose: To illustrate a case of consumption coagulation caused by a hematotoxin-containing snake venom. Method: A case study study describes a snakebite incident managed in the Emergency Department (ED) of a secondary general hospital in Tulungagung, East Java. A 53-year-old male patient presented with pain, swelling, and bleeding in his left thumb, after being bitten by a yellow-brown Bandotan snake, approximately two hours prior to arrival. Results: The patient was given antivenom therapy according to the guidelines. Patients were also given antitetanus, antibiotics, platelet transfusions and fresh frozen plasma (FFP), supportive therapy, and strict monitoring. in the surgical high care unit (HCU). The patient showed improvement on the fifth day and was discharged on the tenth day. Conclusion: The use of local polyvalent antivenom combined with antibiotics, antitetanus therapy, platelets, and FFP transfusion has shown promising results in the management of toxin-induced coagulopathy. Suggestion: Further studies are needed to evaluate the effectiveness of therapy in different age groups, including children, adults, and the elderly. In addition, this study only focused on therapeutic management and did not assess the impact of treatment on organ dysfunction caused by post-treatment lesions.